KB SUNTIK DMPA TERHADAP PERUBAHAN BERAT BADAN DI DESA KARANG JERUK KECAMATAN JATIREJO MOJOKERTO - Ludfiyah, Evie; Adiesti, Ferilia (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2013)
DMPA injectable contraception is a way to prevent pregnancy through hormonal injections of depot medroxyprogesterone acetate containing. There are side effects caused by the use of injectable contraceptives, the most common one is the change in weight on the acceptor. The purpose of this study was to determine the influence of injectable DMPA use KB to changes in body weight in the village of Coral Orange County District Jatirejo Mojokerto. Cross sectional study design used, with a population of 496 acceptors and 83 samples were taken using Simple Random Sampling of respondents, the study was conducted on 7 May to 7 June 2012. The research data was taken using the observation sheet re-visit card KB. After the tabulation of the data were analyzed using Chi Square test with significance level ? = 0.05. The results showed that less than half the respondents who did not use DMPA injectable contraceptives gain weight as much as 31 respondents (37.3%) and a minority of respondents whose weight has not increased or decreased the use of injectable DMPA KB by 4 respondents (5%) . The results of chi square test with significance level ? = 0.05 probability value obtained for 0.008 <? = 0.05 for the H1 accepted that there is influence between the use of injectable DMPA KB of weight change in family planning acceptors and non-DMPA injectable DMPA.Weight gain wasinfluenced by several factors as employment. Acceptor that does not work has little activity can effect changes in weight,anotherfactor that could support such as age, the increasing age of the infrequently performed activities that could affect the metabolic changes in a woman’s body. See the results of this study is the need for awarreness of family planning acceptors and non injectable DMPA to be set lifestile such asdiet and activity to suppress the occurrence of excessive weight gain.Keyword: Use of DMPA Injectable Contraceptives, Weight Changesn